The experience of the Mexican state with the conditional cash transfer programmes to alleviate poverty - Becerril Velasco, Christian Iván (Espacios Públicos; Vol. 18 Núm. 44 (2015): Espacios Públicos, 2022)
For more than fifteen uninterrupted years, conditional cash transfer programmes (ccts) have been used with the purpose of alleviating poverty in Mexico. However, there is little evidence that proves that the programme is achieving its main goal. In recent decades, it has been demonstrated that within developing countries poverty has been alleviated more effectively in countries where the labour market has been strongly institutionalized. Using a mixture of qualitative and quantitative methods, we assessed the extent to which the weakness of the institutional capacities of the Mexican state, among other important factors, has impeded the current Mexican cct programme known as Oportunidades from achieving its main goal. Our results show that the weakness of the institutional capacities of the Mexican state makes poverty alleviation much less likely to occur because it impedes the provision of training and labour market policies that complement the programme and enable the poor to move out of poverty.